Lavender Aromatherapy as a Non-Pharmacological Approach to Managing Pain During the Active Phase of the First Stage of Labor: A Pre-Experimental Study - Masliha (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2025)
Introduction: In the initial stages of labor, especially during the first stage's active phase, mothers experience severe pain, which can be a major hurdle. Objectives: The objective of this study was to evaluate the effectiveness of lavender aromatherapy on pain levels of mothers in active labor. Methods: This research employed a pre-experimental approach with a one-group pre-test post-test design. The sample consisted of 32 mothers in labor who were selected using purposive sampling and met the inclusion criteria. The primary method of data collection was a subjective pain measurement on a numeric scale. The analysis was done using the Wilcoxon test to assess the change of pain levels when lavender aromatherapy was administered. Results: Results: The results showed that after applying lavender aromatherapy, most respondents who initially felt moderate or severe pain were able to reduce the level of pain to mild pain. This change was statistically significant with a p value of 0.000 (p <0.05). Conclusions: This study proves that lavender aromatherapy is effective in managing labor pain in mothers in the active phase. Considering the findings of this study, lavender aromatherapy can be regarded as a simple and efficient non-drug method for managing labor pain.